Percutaneous Electromagnetic Transthoracic Nodule Localization for Ground Glass Nodules - Seung Hwan Song (Korean Society for Thoracic & Cardiovascular Surgery, 2021)
Background: A recent increase in the incidental detection of ground glass nodules (GGNs) has created a need for improved diagnostic accuracy in screening for malignancies. However, surgical diagnosis remains challenging, especially via video-assisted thoracoscopic surgery (VATS). Herein, we present the efficacy of a novel electrical navigation system for perioperative percutaneous transthoracic nodule localization. Methods: Eighteen patients with GGNs who underwent electromagnetic navigated percutaneous transthoracic needle localization (ETTNL), followed by 1-stage diagnostic wedge resections via VATS between January and December 2020, were included in the analysis. Data on patient characteristics, nodules, procedures, and pathological diagnoses were collected and retrospectively reviewed. Results: Of the 18 nodules, 17 were successfully localized. Nine nodules were pure GGNs, and the remaining 9 were part-solid GGNs. The median nodule size was 9.0 mm (range, 4.0–20.0 mm); and the median depth from the visceral pleura was 5.2 mm (range, 0.0–14.4 mm). The median procedure time was 10 minutes (range, 7–20 minutes). The final pathologic results showed benign lesions in 3 cases and malignant lesions in 15 cases. Conclusion: Perioperative ETTNL appears to be an effective method for the localization of GGNs, providing guidance for a 1-stage VATS procedure.